Towards the standardized presentation and publication of small‐angle scattering data from biomolecules in solution. Issue 2 (10th February 2023) - Czjzek, Mirjam
Abstract : The template tables for small‐angle scattering data have been updated by Trewhella et al. [(2023), Acta Cryst. D79 122–132]. Abstract : The template tables for small‐angle scattering data have been updated by Trewhella et al. [(2023), Acta Cryst. D79 122–132].